2018
DOI: 10.3390/medicines5020046
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Pharmaceutical Properties and Value of Astragali Radix

Abstract: Astragali Radix (AR), a Chinese materia medica (CMM) known as Huangqi, is an important medicine prescribed in herbal composite formulae (Fufang) by Traditional Chinese medicine (TCM) practitioners for thousands of years. According to the literature, AR is suggested for patients suffering from “Qi”- and “Blood”-deficiencies, and its clinical effects are reported to be related to anti-cancer cell proliferation, anti-oxidation, relief of complications in cardiovascular diseases, etc. The underlying cell signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 89 publications
0
55
0
Order By: Relevance
“…As we all know, Astragalus membranaceus (AM) was originally described in the Sheng Nong's Herbal Classic which is the Classic of Herbal Medicine in ancient Evidence-Based Complementary and Alternative Medicine traditional Chinese medicine practice. It has a long history of medicinal use as one of the most important qi-tonifying herbs in traditional Chinese medicine [34]. Recently, AM is widely used in clinic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As we all know, Astragalus membranaceus (AM) was originally described in the Sheng Nong's Herbal Classic which is the Classic of Herbal Medicine in ancient Evidence-Based Complementary and Alternative Medicine traditional Chinese medicine practice. It has a long history of medicinal use as one of the most important qi-tonifying herbs in traditional Chinese medicine [34]. Recently, AM is widely used in clinic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As we mentioned above, Astragali Radix is one of the main components of modified HGWD. In TCM theory, Astragali Radix has the effect of tonifying Qi, and Qi deficiency is considered a primary factor for the occurrence of neuropathic pain [36]. Pharmacology studies found that one of the main active components of Astragali Radix, Astragaloside IV (AS-IV), has neuroprotective effects and promotes neovascularization and is also indicated for the prevention of diabetes and its complications because of its decrease in lowing blood glucose and HbA1C levels and increase in insulin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Astragali Radix Bunge (also called as Huangqi in Chinese) has been diffusely utilised as an essential ingredient in over 200 Chinese herb prescriptions to treat weakness, anorexia, chronic fatigue, uterine bleeding, anemia, diarrhea and uterine prolapsed [6,7]. Currently, pharmacological experiments have showed that Astragali Radix possesses a wide variety of biological activities [8], including antioxidant, anti-aging, immunomodulation, anti-in ammation, antitumor, and anti-asthma pharmacological activities [9].…”
Section: Introductionmentioning
confidence: 99%